Incidentally Found Postoperative Spindle Cell Nodule of the Breast 6 Months After Ultrasound-Guided Vacuum-Assisted Excision. Issue 1 (March 2017) - Kim, Yeo Jin; Seo, Mirinae; Sohn, Yu-Mee; Shin, So Youn
Abstract : Abstract: Postoperative spindle cell nodule (PSCN) is a very rare pathologic complication that can occur in association with a recent core needle biopsy, surgery, or trauma. Cases of PSCN have been reported in the lower genitourinary tract, endometrium, and thyroid but are rare in the breast. Herein, we report an ultrasound-guided biopsy-proven PSCN after ultrasound-guided vacuum-assisted excision in the breast.